Hans Urs Von Balthasar tentang Trinitas - Gunawan, Theodorus Christian (Felicitas, 2023)
Theological reflection on the Triune God is one of the branches of Dogmatic Theology. Historically, there have been many reflections from theologians on the mystery of the Trinity. One of these theologians is Hans Urs von Balthasar. Balthasar is one of the most influential contemporary theologians of our time. His thoughts on the Triune God are contained in his various theological works. This paper centers on Hans Urs von Balthasar's reflections on the Trinity. His reflections on the Triune God are centered on the work of salvation, especially in the mystery of the Incarnation and the total self-giving of the Son of God in the passion, death, and resurrection, which is then believed by Christians as the Feast of Easter.